تاريخ المغرب العربي: ليبيا وتونس والجزائر والمغرب من الفتح العربي حتى قيام دولة الأغالبة والرستميين والادارسة - زغلول, سعد عبد المجيد (دار المعارف, 1964)
Keywords: Dynastie rustumide

Coercitio: Staat und Kirche im Donatistenstreit - Grasmück, Ernst Ludwig (L. Röhrscheid, 1964)
Keywords: Donatisme

Donatisten und Katholiken: soziale, wirtschaftliche und politische Aspekte einer nordafrikanischen Kirchenspaltung - Tengström, Emin (Elanders Boktr, 1964)
Keywords: Donatisme

No more for ever : a Saharan Jewish town ; with appendices on physical anthropology, demography and social structure - Briggs, Lloyd Cabot (Peabody Museum, 1964)
Keywords: Judaïsme – Djerba

Islam in East Africa - Trimingham, J. Spencer (Clarendon Press, 1964)
Keywords: Zanzibar

Katalog rekopisów arabskich - Dembsky, W. (1964)
pp. 72, 77-89 (Ibāḍī MSS)
Keywords: Catalogue – Cracovie

Dīwān al-Sitālī - Sitālī, Abū Bakr Aḥmad b. Saʿīd al-Kharūṣī al- (al-Maṭb. al-ʿUmūmiyya, 1964)
réimp. 2005 (MNHC)

Jalā’ al-ʿUmy. Sharḥ Mīmiyyat al-Dimā li’l-Shaykh Khalfān b. Jumayyil al-Siyābī al-ʿUmānī - Siyābī, Khalfān b. Jumayyil al- (al-Maṭb. al-ʿUmūmiyya, 1964)
Commissioned by ʿAbdallāh. b. ʿAlī al-Khalīlī wa-Tilmīdhihi (Abī Surūr) Ḥumayyid b. ʿAbdallāh.

al-Ibāḍiyya fī Mawkib al-Tārīkh: al-Ibāḍiyya fī Lībyā - Muʿammar, ʿAlī Yahyā (1964)
Keywords: Ouvrages de vulgarisation

al-Ibāḍiyya fī Mawkib al-Tārīkh: al-Ibāḍiyya fī Lībyā - Muʿammar, ʿAlī Yahyā (1964)
Keywords: Ouvrages de vulgarisation

al-Faṣl fī ‘l-Milal wa’l-Ahwā’ wa’l-Niḥal … wa-maʿahu al-Milal wa’l-Niḥal li’l-Shahrastānī - Ibn Ḥazm, al-Ẓāhirī al-Andalusī (Makt. wa-Maṭb. Muḥammad ʿAlī Ṣubayḥ wa-Awlādihi, 1964)

Eastern Arabian frontiers - Kelly, J.B. (Faber and Faber, 1964)
Don JCW (mars 2026)

Muḥāḍarāt ʿan il-Taṭawwur al-Siyāsī al-Ḥadīth li-Qaḍiyyat ʿUmān - Dāwud, Maḥmūd ʿAlī (Jāmiʿat al-Duwal al-ʿArabiyya, 1964)
Keywords: Vie politique – Oman – 1932-1970

Ṣafaḥāt Khālida min al-Jihād - Bārūnī, Zaʿīma Sulaymān al- (Maṭābiʿ al-Istiqlāl al-Kubrà, 1964)
Keywords: Bārūnī; Sulaymān al- (1870-1940)

al-Ibāḍiyya fī Mawkib al-Tārīkh: Nash’at al-Madhhab al-Ibāḍiyya - Muʿammar, ʿAlī Yahyā (1964)
Keywords: Ouvrages de vulgarisation

ʻAlī and Muʻāwiya in early Arabic tradition: studies on the genesis and growth of Islamic historical writing until the end af the ninth century - Petersen, Erling Ladewig (Munksgaard, 1964)
"The first civil war 656-61 and the party antagonisms emerging from it have proved to be of crucial importance to the development of Islam. No wonder, then, that subsequent interpretations of the 'Ali-Mu'āwiya conflict provoked serious misrepresentations of the actual course of events. In a previous study I have tried to reconstruct some trends and problems of this conflict on the basis of the primary sources. This book presents an attempt to trace the formation of the historical tradition associated with the first civil war by applying modern standards of historical method. I have finally tried to establish an outline of the genesis of 'profane' historical writing in Islam, in so far as the 'Ali-Mu'āwiya conflict can be considered paradigmatic. The book thus aims at combining a 'historiographical' and methodical study of the early conflicts in Islam"–
Keywords: Fitnah

Exiles in the Sahara - Frost, Kelman (Abelard-Schuman, 1964)
The Chebka, that part of the Sahara into which twelve-year-old Hassoun and his people fled, is now known as the M'Zab, and the people living there, direct descendants of the Ibadites, are usually called Mozabites. This story tells of the founding in the the eleventh century of El-Ateuf, the first Mozabite settlement after their exile in the desert within a desert.
Keywords: Littérature – Mzab